KERJASAMA INDONESIA - WORLD BANK DALAM PENGELOLAAN PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS II) DI FLORES PERIODE 2013-2017 - Marsyadita Urtadiputri, - (2018)
This research is conducted to present research on "Indonesia-World Bank Cooperation in Community-Based Drinking Water and Sanitation Program Management (PAMSIMAS II) period 2013-2017" as this cooperation is conducted to assist Indonesia in providing universal access for rural communities. The formulation of the problem in the study questioned "how form the cooperation of the Indonesian government with the World Bank in PAMSIMAS II program period 2013-2017". To answer the research question, the author uses the framework of the theory of National Interest, International Cooperation, Foreign Aid and Technical Assistance. The author uses a qualitative method in which the author attempts to explain Indonesia's cooperation with the World Bank in the drinking water and sanitation (PAMSIMAS II) program and collect primary and secondary data through interviews and data analysis. In cooperation between Indonesia and the World Bank has provided significant results in the provision of drinking water and sanitation in Indonesia